Предмет: Математика,
автор: вайфай5634872
решите пожалуйста срочно
Приложения:
Ответы
Автор ответа:
0
b) х + 2 3/8 = 5 1/4 - 1 3/8
х = 5 1/4 - 1 3/8 - 2 3/8
х = (5 - 1 - 2) + (1/4 - 3/8 - 3/8) = 2 + (2/8 - 6/8) = 2 + (- 4/8) = 2 - 1/2 = 1 1/2
х = 5 1/4 - 1 3/8 - 2 3/8
х = (5 - 1 - 2) + (1/4 - 3/8 - 3/8) = 2 + (2/8 - 6/8) = 2 + (- 4/8) = 2 - 1/2 = 1 1/2
Похожие вопросы
Предмет: Английский язык,
автор: evgeniakopytova737
Предмет: ОБЖ,
автор: velichkoaliona660
Предмет: Русский язык,
автор: anyt14
Предмет: Экономика,
автор: klinovanatalija